Richard III - Hill, Stuart (London Scholastic Children's Books, 2014)
I WAS THERE... RICHARD III tells the thrilling story of England's last Plantagenet king in his youth. Brilliantly reimagined, readers aged 7+ will love this vivid first-hand account of a child's experience of knights, castle life and an exciting battle. The perfect read for children intrigued by the recent media coverage of Richard III's exhumation and reburial in 2014.
Formerly CIP.
Keywords: Richard -- III, -- King of England, -- 1452-1485 -- Juvenile fiction; Great Britain -- History -- Lancaster and York, 1399-1485 -- Juvenile fiction; Children's stories; Historical fiction